Konsep cinta dalam antologi cerkak Rembulan Bali Ndadari karya Harwimuka - Wulantari, Ayu; Fuadhiyah, Ucik (Universitas Mulawarman, 2025)
This research analyzes the concept of love in the anthology of the cerkak of “Rembulan Bali Ndadari” by Harwimuka using Robert J. Sternberg’s theory of love psychology. This theory explains that love consists of three main components: intimacy, passion, and decision or commitment, which can result in different types of love. This research was conducted using a qualitative descriptive method with content analysis techniques. The research data is in the form of texts from nine stories in the anthology selected purposively based on their relationship with the theme of love. The analysis results show that the characters in the cerkak of “Rembulan Bali Ndadari” represent a combination of three components of love that produce four types of love. The four types of love include pleasure, brotherly, romantic, and perfect love. This finding illustrates the dynamics of the relationship between characters based on Sternberg’s theory of love. This research contributes to understanding the concept of love in literary works through a psychological approach, especially the psychology of love.